The Arab-Israeli Peace Process : Lessons for India and Pakistan - Edited by Ahmar, Moonis (Karachi Oxford University Press, 2002)
This title compares conflict and co-operation in the context of the Arab-Israeli and India-Pakistan peace processes and examines the important similarities and contradictions in this regard. It also discusses the role of third party mediation, the nuclear factor, the role of external factors, and the military and economic dimensions of the two processes.
Include Tables and Index
Keywords: Peace -- Pakistan -- Arab-Israeli Conflict--Peace -- Diplomatic Relations